Pediatric Kaposi sarcoma in context of the HIV epidemic in sub-Saharan Africa: current perspectives - El-Mallawany NK; McAtee CL; Campbell LR; Kazembe PN (Dove Medical Press, 2018)
Nader Kim El-Mallawany,1,2 Casey L McAtee,1,2 Liane R Campbell,3 Peter N Kazembe4,5 1Department of Pediatrics, Section of Hematology and Oncology, Baylor College of Medicine, Houston, TX, USA; 2Texas Children’s Cancer and Hematology Centers, Houston, TX, USA; 3Department of Pediatrics, Baylor College of Medicine Children’s Foundation Tanzania, Baylor International Pediatric AIDS Initiative at Texas Children’s Hospital, Mbeya, Tanzania; 4Department of Pediatrics, Baylor College of Medicine Children’s Foundation Malawi, Baylor International Pediatric AIDS Initiative at Texas Children’s Hospital, Lilongwe, Malawi; 5Department of Pediatrics, Kamuzu Central Hospital, Lilongwe, Malawi Abstract: The global experience with pediatric Kaposi sarcoma (KS) has evolved immensely since the onset of HIV (human immunodeficiency virus). In this review, current perspectives on childhood KS are discussed in the context of the HIV epidemic in sub-Saharan Africa. Endemic (HIV-unrelated) KS was first described over 50 years ago in central and eastern Africa, regions where human herpesvirus-8, the causative agent of KS, is endemic. With the alarming rise in HIV prevalence over the past few decades, KS has become not only the most common HIV-related malignancy in Africa, but also one of the most common overall childhood cancers throughout the central, eastern, and southern regions of the continent. The unique clinical features of pediatric KS that were described in those early endemic KS reports have been re-affirmed by the contemporary experience with HIV-related KS. These characteristics include a predilection for primary lymph node involvement, significant proportions of patients lacking prototypical cutaneous lesions, and the potential for fulminant disease progression. Other clinical features that distinguish childhood KS from adult disease include disease presentation with severe cytopenias, and the common occurrence of childhood KS without severe CD4 count suppression. Distinct clinical heterogeneity in disease presentation and treatment response have been demonstrated. Long-term complete remission and event-free survival can be achieved—especially in children with lymphadenopathic KS—utilizing treatment with antiretroviral therapy plus mild–moderate chemotherapy regimens that are well tolerated, even in low-income settings. A pediatric-specific staging classification and risk-stratification platform have been retrospectively validated, and may help guide therapeutic strategies. With expansion of the HIV treatment infrastructure throughout Africa, coupled with recent developments in establishing comprehensive pediatric oncology programs, there is great potential for improving outcomes for children with KS. Increased awareness of the unique clinical nuances and collaborative evaluations of pediatric-specific treatment paradigms are required to optimize survival for children with KS. Keywords: Kaposi sarcoma, pediatric KS, HHV-8, KSHV, pediatric oncology, global health